Pengaruh Store Atmosphere, Lokasi dan Variasi Menu Terhadap Keputusan Pembelian di Pempek G Putra - Genesius; Joseph M.J. Renwarin (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Pempek in the Kemayoran area has a unique product taste, which is a taste that fits the taste of Jakarta people without losing its Palembang specialty that cannot be found elsewhere. There are also many small and medium-sized pempek businesses there, one of which is Pempek G Putra, which has been selling since 1990. This study aims to see whether the variables storing atmosphere, location and menu variations have a significant effect on purchasing decisions in Pempek G Putra amidst many rivals. The survey method with questionnaires through google form to 201 respondents, data filling techniques purposive sampling and non-probability sampling techniques, the results were tested with SPSS version 25. The results showed that the menu variation variables significantly influence purchasing decisions in Pempek G Putra, while the atmosphere store and location have no significant effect on purchasing decisions. Pempek G Putra can do decorations when there are certain events by using the services of an event organizer and must keep the parking lot clean by making cleaning schedules for employees.